2013
DOI: 10.3892/br.2013.56
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between the FAS/FASL polymorphisms and cervical cancer risk: A meta-analysis

Abstract: Abstract. FAS/FASL gene promoter polymorphisms are associated with cervical cancer risk, however, results from previous studies have been conflicting. To obtain a more precise estimation of the association between these polymorphisms and cancer risk, a meta-analysis was performed. All eligible studies up to November 1st, 2012, concerning FAS-670 A/G, FAS-1377 G/A and FASL-844 T/C polymorphisms and cervical cancer risk, were collected from the following electronic databases: PubMed, Excerpta Medica Database and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In addition, Zoodsma et al (2005) showed a relationship between FasR 670A ‡G and increased risk of adenocarcinoma and not squamous cell carcinoma of the cervix. However, in another study conducted in Chinese women, as well as in Caucasian populations, there was no association between Fas SNPs and cervical cancer susceptibility (Chen et al, 2013;Du et al, 2013;Engelmark et al, 2004b;Pavlidou et al, 2016;Sun et al, 2005) resonating with the findings from African populations (Table 3).…”
Section: Fas Cell Death Receptorsupporting
confidence: 46%
See 1 more Smart Citation
“…In addition, Zoodsma et al (2005) showed a relationship between FasR 670A ‡G and increased risk of adenocarcinoma and not squamous cell carcinoma of the cervix. However, in another study conducted in Chinese women, as well as in Caucasian populations, there was no association between Fas SNPs and cervical cancer susceptibility (Chen et al, 2013;Du et al, 2013;Engelmark et al, 2004b;Pavlidou et al, 2016;Sun et al, 2005) resonating with the findings from African populations (Table 3).…”
Section: Fas Cell Death Receptorsupporting
confidence: 46%
“…The Fas receptor (FasR) also known as CD95 is a tumor necrosis factor that activates downstream apoptotic activity through interaction with Fas ligand (FasL) (Du et al, 2013). Viral infection mediates an immune transactivation of the caspase cascade, thus inducing activation induced cell death (Siegel, 2006;Ueda et al, 2006).…”
Section: Fas Cell Death Receptormentioning
confidence: 99%
“…Although the FAS polymorphisms have been widely investigated their association with multiple tumors susceptibility 30 31 32 , the studies on mechanisms underlying the association were limited. The rs2234767 and rs1800682 polymorphisms can alter the SP1 and STAT1 binding site, leading to downregulated FAS expression 13 14 .…”
Section: Discussionmentioning
confidence: 99%